Near-infrared responsive polycaprolactone coatings for magnesium implants: Photodynamic antibacterial and controllable dissolution - Xi Liu; Jinglong Pan; You Lv; Xu Wang; Xiaoze Ma; Xinxin Zhang; Guangyi Cai; Zehua Dong (Journal of Magnesium and Alloys)
Magnesium implants have received widespread attention in orthopaedic surgery. However, the mechanical degradation and concurrent inflammation caused by the rapid corrosion of Mg limits their applications. In this study, a kind of unique core-shell heterojunction CuS@PPy nanostructures was synthesized and then incorporated in polycaprolactone (PCL) to construct an intelligent coating (CuS@PPy/PCL) on micro-arc-oxidized Mg implants. The PCL-based coating can realize near-infrared (NIR)-driven antibacterial and controllable Mg dissolution according to different bone healing stages. At the beginning of bone remodelling, the coating exhibits promising antibacterial properties with 99.67% and 99.17% efficacy against S. aureus and E. coli, respectively, thanks to the singlet oxygen (1O2) and alkoxyl radicals (RO·) generated by the photodynamic effect of CuS@PPy heterojunction under low-power NIR light (1.5 W/cm2). In the bone reparative stage, the PCL-based coating can maintain high corrosion resistance to meet the mechanical requirements of Mg implants in human body fluid. However, after the complete rehabilitation of bones, through a high-power (2 W/cm2) NIR light, the PCL-based coating changed from an elastic to a viscous flow state (44.7 °C) under the photothermal effects of CuS@PPy, leading to quick degradation of the PCL-based coating and following accelerating dissolution of the Mg implant (avoiding secondary surgery). Hopefully, this NIR-responsive coating may provide an innovative method for the antibacterial and controllable dissolution of Mg implants.